Babylon. Wissenskultur in Orient und Okzident - Marzahn, Joachim (Topoi, 2011)
In this collection of interdisciplinary papers, for the first time well-known scholars of Ancient Near Eastern Studies discuss Babylon from the point of view of the ""culture of knowledge"". The volume is the result of a conference that took place on the occasion of the exhibition Babylon ? Truth and Myth in Berlin. For the contemporary cultures of the Ancient World, Babylon was the epitome of learned scholarship. Yet in the processes of transformation of Late and post-Antiquity, to the same extent to which this culture of knowledge was forgotten after the collapse of the old oriental empires, Babylon became symbolic for the occult, for magic and esoteric knowledge. As the first joint pilot project by Topoi and the publisher De Gruyter for the simultaneous publication in print and open access, this volume will, on publication, also be available via www.reference-global.de as an eBook ""open access"".; Eva Cancik-Kirschbaum, Freie Universit